The Gap Between the Perceptions and Expectations of Quality of Services Delivered to the Participants at the Scientific Conferences Using the University of Hafr Al Batin as a Model - Alharbi, Abdullah Muzil; Alshammari, Adel Ayed; Naqvi, Hasnain Abbas (Frontiers in Psychology, 2022)
This study aims to reveal the gap between the perceptions and expectations of the quality of the services delivered to the participants at the scientific conferences held at the emerging Saudi universities (University of Hafr Al Batin as a model). The study also reveals if there are differences, with statistical significance, in the sample response due to several such variants as gender, nationality, and the attendance rate of conferences per year. The research adopts the descriptive approach and uses SERVQUAL instruments. It has been applied to a random sample of (155) persons. The study outcomes show that the expectations are higher than the perceptions in terms of all dimensions. It also demonstrates the differences that exist due to the attendance rate of conferences per year in favor of those who attended 3 or more conferences. The study provides suggestions to raise the quality of the services delivered to the participants at these conferences.